Encyclopaedia of religion and ethics; v. 8 - Hastings, James; Selbie, John A.; Gray, Louis H. (Edinburgh, Scotland T and T Clark, 1915)
Contents : v. 8 : Life and death - Mulla
Keywords: Religion; Ethics